2010
DOI: 10.1007/s11096-010-9380-2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapeutic review and update of idiopathic nephrotic syndrome in children

Abstract: The wide range of options available for the pharmacotherapeutic management of NS and the lack of evidence about the comparative efficacy and safety of the different therapeutic strategies, make its positioning rather difficult. Therefore each hospital needs to draw up protocols based not only on the small amount of evidence available, but also on the authorized indications, availability of the drugs, clinical experience, associated costs, and patient preferences with regard to the duration of treatment, incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
0
6
0
6
Order By: Relevance
“…Interestingly, a recent survey to assess management of childhood-onset NS among 30 American pediatric nephrologists from ten institutions showed that 48% of respondents preferred alkylating agents and 37% calcineurin inhibitors for SDNS [37]. However, MMF was proposed as a possible alternative to anticalcineurins for second-line (after steroids) therapy of SDNS by the Children's Nephrotic Syndrome Consensus Conference in 2009 [38] and by Manrique-Rodriguez et al in 2010 [39]. Our report strongly supports the proposal that MMF be given before calcineurin inhibitors, considering its efficiency and its lack of nephrotoxicity and cosmetic effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a recent survey to assess management of childhood-onset NS among 30 American pediatric nephrologists from ten institutions showed that 48% of respondents preferred alkylating agents and 37% calcineurin inhibitors for SDNS [37]. However, MMF was proposed as a possible alternative to anticalcineurins for second-line (after steroids) therapy of SDNS by the Children's Nephrotic Syndrome Consensus Conference in 2009 [38] and by Manrique-Rodriguez et al in 2010 [39]. Our report strongly supports the proposal that MMF be given before calcineurin inhibitors, considering its efficiency and its lack of nephrotoxicity and cosmetic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, mizoribine, a purine-metabolism inhibitor that mimics MMF, has been shown to induce a significant reduction of prednisolone dose and relapse rate in nine of ten children with SDNS who had received neither cyclophosphamide nor cyclosporine previously [42]. Therefore, cyclophosphamide, because of its adverse effects and relatively low efficacy in SDNS [34][35][36], should now rather be positioned after MMF and cyclosporine, as proposed [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…[4,22]. Ad a, vomit, anorexia, abdominal distention, reduction of leukocyte, liver dysfunction and influences on menstrual cycle of female patients of childbearing age [9,12,17].…”
Section: Discussionmentioning
confidence: 99%
“…Steroid dirençli hastalarda; kullanılabilen başlıca diğer immünsüpresif ilaçlar; alkilleyici ilaç grubu, örneğin; siklofosfamid, klorambusil, kalsinörin inhibitörleri (CNIs), siklosporin and takrolimus, mikofenolat mofetil (MMF), rituksimab ve adrenokortikotropik hormon (ACTH) olarak sıralanabilir. 17 Steroid dirençli hastalarda alkilleyici ilaçlar tedaviye eklenebilmektedir. Alkilleyici tedaviler; genellikle nefrotik düzeyde proteinüri varlığında böbrek fonksiyonları normal ve normale yakın ise tercih edilmektedir.…”
Section: İdi̇yopati̇k Nefroti̇k Sendrom Tedavi̇si̇nde İmmünopatogenezi̇n Etunclassified